2012
DOI: 10.1111/j.1756-2589.2012.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Theoretical Model of Intimate Partner Violence, Coparenting After Separation, and Maternal and Child Well‐Being

Abstract: The quality of coparenting relationships after separation is known to affect mothers' and children's physical and mental health. It is well established that conflict is a common phenomenon among separating parents; however, studies rarely distinguish between relationships characterized by violence as opposed to conflict. Because violence creates a distinct separation and coparenting experience, we propose a theoretical model that integrates these disparate literatures. The integrated model provides a heuristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 64 publications
2
36
0
Order By: Relevance
“…Poor quality coparenting relationships have been associated with negative effects for mothers and children (e.g., Fabricius & Luecken, 2007; Whiteside & Becker, 2000). Consistent with Hardesty et al (2012), we demonstrated that both divorce- and violence-related perceptions and experiences influence mothers’ coparenting relationships with their former partners. For example, results of multivariate analyses with the full sample highlight the importance of positive feelings toward fathers in general (divorce variable) and perceived threat of future harm (violence variable) for predicting coparenting quality.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Poor quality coparenting relationships have been associated with negative effects for mothers and children (e.g., Fabricius & Luecken, 2007; Whiteside & Becker, 2000). Consistent with Hardesty et al (2012), we demonstrated that both divorce- and violence-related perceptions and experiences influence mothers’ coparenting relationships with their former partners. For example, results of multivariate analyses with the full sample highlight the importance of positive feelings toward fathers in general (divorce variable) and perceived threat of future harm (violence variable) for predicting coparenting quality.…”
Section: Discussionsupporting
confidence: 81%
“…As posited by Hardesty and colleagues (2012), postseparation dynamics and the quality of coparenting relationships will be influenced by type of IPV experienced in marriage. To investigate this, an examination of coercive control is necessary.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In addition to concern about effects of children's exposure to his abuse against her (Overbeek, de Schipper, Lamers-Winkelman, & Schuengel, 2013), she may fear for the child's safety at his hand (Macmillan, Wathen, & Varcoe, 2013) or punitive measures by children's services and potential apprehension (Nixon, Radtke, & Tutty, 2013). These are each elevated in the context of a potential separation and when custody is in dispute (Austin, Fieldstone, & Pruett, 2013), as well as following separation when he has access to the children (Hardesty et al, 2012).…”
Section: Child-related Issuesmentioning
confidence: 94%
“…There is a great deal of literature on safety issues for children and women's efforts to secure their children's safety when they are in an abusive relationship (e.g., Overbeek et al, 2013;Macmillan et al, 2013), in particular during and following a separation where custody and access are in dispute (Austin et al, 2013;Hardesty et al, 2012). In addition, women's relationships with friends (Ahmad et al, 2007), family members (Zink et al, 2006) and neighbors (Renzetti, 2009) were similarly noted.…”
Section: Community Involvementmentioning
confidence: 99%
“…Coparenting studies rarely focus on marital IPV as distinct from conflict, or, when they do, they ignore different types of IPV. Further, longitudinal coparenting studies have not considered how marital IPV may relate to variations in coparenting trajectories (Hardesty, Raffaelli, Khaw, Mitchell, Haselschwerdt, & Crossman, 2012). The current study fills these gaps by examining how marital IPV predicts change and variability in coparenting relationships in the first year after a divorce filing.…”
mentioning
confidence: 99%